2012
DOI: 10.1016/j.brainres.2012.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Clavulanic acid inhibits MPP+-induced ROS generation and subsequent loss of dopaminergic cells

Abstract: Clavulanic acid is a psychoactive compound that has been shown to modulate central nervous system activity. Importantly, in neurotoxin-induced animal models, clavulanic acid has been shown to improve motor function (Huh et al., 2010) suggesting that it can be neuroprotective; however, the mechanism as how clavulanic acid can induce neuroprotection is not known. We demonstrate here that clavulanic acid abrogates the effects of the neurotoxin 1-methyl-4-phenylpyridinium (MPP+) which mimics Parkinson’s disease (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Further, the development of behavioral sensitization to morphine is thought to be more dependent on glutamate transmission than on dopamine transmission (Vanderschuren and Kalivas, 2000). Although it is somewhat difficult to reconcile the behavioral effects of CA observed here with its dopamine-enhancing effects (Sanna et al, 2013; Kost et al, 2011, 2012), it should be noted that our study used a dosing paradigm in which CA was administered repeatedly. This dosing paradigm was used because multiple laboratories have demonstrated that the preclinical activity of CTX in reducing the symptoms of CNS diseases is dependent on repeated administration (Rothstein et al, 2005; Sari et al, 2009, 2013; Rawls et al, 2007, 2010a, b; Tallarida et al, 2013; Trantham-Davidson et al, 2012).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Further, the development of behavioral sensitization to morphine is thought to be more dependent on glutamate transmission than on dopamine transmission (Vanderschuren and Kalivas, 2000). Although it is somewhat difficult to reconcile the behavioral effects of CA observed here with its dopamine-enhancing effects (Sanna et al, 2013; Kost et al, 2011, 2012), it should be noted that our study used a dosing paradigm in which CA was administered repeatedly. This dosing paradigm was used because multiple laboratories have demonstrated that the preclinical activity of CTX in reducing the symptoms of CNS diseases is dependent on repeated administration (Rothstein et al, 2005; Sari et al, 2009, 2013; Rawls et al, 2007, 2010a, b; Tallarida et al, 2013; Trantham-Davidson et al, 2012).…”
Section: Discussionmentioning
confidence: 88%
“…Some of the effects of CTX are prevention of analgesic tolerance and physical dependence that develops during chronic morphine exposure (Rawls et al, 2007, 2010a, b), inhibition of opioid-induced hyperalgesia (Chen et al, 2012), inhibition of relapse to cocaine seeking (Knackstedt et al, 2010; Sari et al, 2009), inhibition of the direct reinforcing effects of cocaine in mice maintained under a progressive-ratio responding schedule (Ward et al, 2011), inhibition of locomotor sensitization produced by cocaine and amphetamine (Tallarida et al, 2013; Sondheimer and Knackstedt, 2011; Rasmussen et al, 2011), prevention of methamphetamine-induced CPP (Abulseoud et al, 2013), and reduction of alcohol consumption (Sari et al, 2013; Rao and Sari, 2012). Despite structural similarities between CA and CTX, and the more favorable pharmacokinetic and physiochemical properties of CA as related to CNS activity (Nakagawa et al, 1994; Bolton et al, 1986), the potential effectiveness of CA as a therapeutic for CNS diseases is limited to studies that have examined neuroprotection, anxiety, and erectile dysfunction (Kim et al, 2009; Kost et al, 2011, 2012; Sanna et al, 2013). To our knowledge, the present results are the first evidence that CA can disrupt rewarding and sensitizing effects of an addictive substance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CA is used as an adjuvant for other BLMs antibiotic effects as it has a negligible antibiotic effect by itself but it inhibits the β-lactamase molecules, the main resistance mechanism for BLMs. 19 Similarly to CFX, CA induces GLT1 overexpression, 7 and also has numerous effects in the central nervous system (CNS), for example it induces dopamine and serotonin release, 27 is neuroprotective, 28 , 29 has anxiolytic properties, 30 and shows medullary dopaminergic modulation. 31 Also, acute antiallodynic effect was previously reported in inflammatory pain models 32 where a significant effect of CA administration in the acute phase of the formalin test was reported.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that MPP + induces MMPs loss (Kost et al, ; Xu et al, ). DJ‐1 is one of the genes associated with mitochondria in PD, and its loss of function is associated with MMP downregulation and fragmentation (Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%